Practice in industry training in fish culture - Delgado, Catalino C. (College of Fisheries, University of the Philippines, 1956)
After two years of concentrated theoretical study and field work in his chosen course, a student in the Philippine Institute of Fisheries Technology must undergo "Practice-In-Industry" training for six months before he graduates. This six-month-apprenticeship is of utmost importance to the students because it is the time when he puts into practice what he has learned in the theory. At this time he meets people in the business and learns from them business know how based from their experiences. What problems might have been vague when he was in the classroom are made clear when he meets them in the field. Such problems when met must be solved without the guidance of his instructors. In other words, it is this time when the student begins to stand on his own feet. With his two years of theoretical study the student is technically equipped when he goes out of school to manage his own pond or employ in a fishery project.